Role of Surgery in Endometriosis-Associated Subfertility - Berlanda, Nicola; Vercellini, Paolo; Somigliana, Edgardo; Frattaruolo, Maria Pina; Buggio, Laura; Gattei, Umberto (Seminars in Reproductive Medicine, 2013)
Analysis of published series reveals that no more than a fourth of subfertile patients undergoing surgery for peritoneal endometriotic implants, rectovaginal endometriotic lesions, or recurrent endometriomas achieved conception spontaneously. First-line surgery for ovarian endometriotic cysts appears associated with a better reproductive performance, that is, a mean postoperative pregnancy rate of ∼50%. At the same time, excision of endometriomas paradoxically seems to induce gonadal damage. With the exception of peritoneal disease, no randomized trials are available to assess the effect of surgery in subfertile women with endometriosis. Therefore, it is not possible to define the absolute benefit increase of the treatment of ovarian and rectovaginal lesions. The decision to undergo surgery for endometriosis-associated subfertility must be shared with the woman after detailed information and taking into account several additional conditions, such as presence of pain, large or complex adnexal masses, bowel or ureteral stenosis, and coexisting infertility factors. When considering surgery, a therapeutic equipoise should be reached that includes demonstrated benefits, potential morbidity, and costs of treatment alternatives. Particularly in case of recurrent endometriosis, in vitro fertilization should generally be preferred to surgery. The role of surgery in endometriosis-associated subfertility includes temporary pain relief in symptomatic women desiring a spontaneous conception.
Keywords: endometriosis; infertility; surgery; laparoscopy; ovarian cyst